Effect of single dose alcohol administration on malondialdehyde, glutathione,total protein and hydroxproline levels of rat liver - Sibel DİNÇER and Eser ÖZ and Seren ÖZENİRLER (Turkish Journal of Gastroenterology, 2019)
-